(untitled) (Revista Electrónica REDINE, 2018)
The elements that support the strategic direction and organizational culture are the mission, vision and values ​​declared in the Philosophy of Management, the objective of this research is to define for the Coordination Internship Program Agroindustrial Engineering Centroccidental University "Lisandro Alvarado ". Thinking generate a model organization within the units internship universities in the region, along with proper promotion encourages self-management. The proposal was based on the methodology of strategic planning and Marlene R. Fred R. Davis Potellá starting with identifying the mission, vision and values ​​of the institution. The lifting of the information was based on instruments designed by the authors and brainstorming technique applied in meetings in which users internships unit match. So information that answers questions get: what are we?, what we expect to be? responses reflected in the mission and vision, basic elements of the institutional horizon. Finally, it was found that the statement of management philosophy internship coordination leads to an understanding of the functions and scope of management projecting the future.